Pengaruh Mutu Pelayanan terhadap Kepuasan Pelanggan pada Suru-Suru All Delivery Panyabungan Kabupaten Mandailing Natal - Muhammad Fauzan; Ade Khadijatul Z Hrp; Muhlisah Lubis (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the influence of service quality on customer satisfaction at Suru-Suru All Delivery Panyabungan, Mandailing Natal Regency. The type of research is quantitative research. Data collection techniques are by observation and distributing questionnaires. This research involved a sample of 86 respondents using the Slovin formula. All tests were carried out using the SPSS version 25 program. The results of this research were that service quality had a partial effect on customer satisfaction at Suru-Suru All Delivery Panyabungan, Mandailing Natal Regency. The partial test value (t) on the service quality variable (X) was 3.769 with a value ttable is 1.663. So the tcount value is greater than ttable (3.768 > 1.663), then the service quality variable (X) has a positive and significant impact on customer satisfaction (Y). This shows that the first hypothesis (Ha) is accepted. This means that "the service quality variable has a positive and significant effect on customer satisfaction" which has also been proven successfully by this research with an R Square value obtained of 0.145 multiplied by 100% to 14.5%. while 85.5% is explained by other variables. Apart from that, the service quality variable has a low relationship with customer satisfaction at Suru-Suru All Delivery, Panyabungan District, Mandailing Natal Regency, amounting to 0.380.